2017
DOI: 10.1111/apa.14021
|View full text |Cite
|
Sign up to set email alerts
|

Low age, low birthweight and congenital heart disease are risk factors for intensive care in infants with bronchiolitis

Abstract: Less than 0.1% of infants under the age of 12 months were admitted to the PICU for bronchiolitis. Low age, low birthweight or prematurity and CHD were independently significant risk factors for both intensive care and respiratory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
5
21
0
5
Order By: Relevance
“…In our study, infants aged < 1 year accounted for 97% of all admissions to our PICU with bronchiolitis. The majority of our cases were infants aged ≤ 2 months ( n = 150), and 70% of these were RSV positive, suggesting that younger infants are more vulnerable to severe RSV disease, which is consistent with the findings from previous studies [ 12 , 18 , 28 ].The association of younger age and prematurity with an increased risk of PICU admission was not unexpected and has been well described previously.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, infants aged < 1 year accounted for 97% of all admissions to our PICU with bronchiolitis. The majority of our cases were infants aged ≤ 2 months ( n = 150), and 70% of these were RSV positive, suggesting that younger infants are more vulnerable to severe RSV disease, which is consistent with the findings from previous studies [ 12 , 18 , 28 ].The association of younger age and prematurity with an increased risk of PICU admission was not unexpected and has been well described previously.…”
Section: Discussionsupporting
confidence: 92%
“…passive smoking, crowded household) and presence of co-morbidities (e.g. chronic pulmonary disease, congenital heart disease, immunodeficiency, neurologic disease) [ 4 , 18 , 28 , 31 ]. However, few studies have yet described factors associated with PICU admission and outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In two Finnish studies, the PICU treatment rate was 6% among infants hospitalised for bronchiolitis at ages less than 12 months or less than 6 months . Low birthweight, low gestational age and congenital heart disease are well‐known risk factors for intensive care and respiratory support in infants with bronchiolitis . In the present study, infants who did not respond sufficiently to HFNC treatment and needed another more effective method of respiratory support were more likely to be born preterm, with lower gestational age and birthweight.…”
Section: Discussionmentioning
confidence: 52%
“…We also noted that the percentage of RSV infection gradually decreased with age, which suggests that younger infants are more vulnerable to RSV disease; this is consistent with the findings of previous studies. 18,19 A retrospective cohort study indicated that the reduced exposure of pregnant women to RSV epidemic contributed to more severe RSV-induced bronchiolitis in children under 6 months of age. 20 Therefore, RSV-induced bronchiolitis is common in 6 months age; this may be associated with the circulation of antibodies that are not associated with RSV infection during pregnancy.…”
Section: Discussionmentioning
confidence: 99%